Schrecksekunde – was bedeutet diese Lücke? - Keller, Frieder (DMW - Deutsche Medizinische Wochenschrift, 2019)
Ludwig van Beethoven’s Opus 119 represents a series of “bagatelles” for piano. On closer inspection, or better listening, one can get to the thought: How should one interpret the pause that the Maestro has woven into bar 65 of the first piece?
Keywords: Ludwig van Beethoven; Bagatelle; Opus 119; Schrecksekunde